High school training outcome and academic performance of first-year tertiary institution learners - Taking 'Input-Environment-Outcomes model' into account - Bianca Ifeoma Chigbu (Heliyon, 2021)
This study attempted to decipher the link between students' input, output, learning environment, challenges, and students' demographic variables at the tertiary level of education. First-year undergraduate students (n = 122) were surveyed with a structured questionnaire. As hypothesized in the input-environment-outcomes model adopted in this study, students' academic input and learning environment shape learners' study outcomes. Findings revealed that learners' academic performance is influenced by students' demographic variables, intellectual input, educational environment, and challenges, but most importantly, an excellent and effective study environment is what makes the most remarkable difference in the learner's scholastic achievement. If an academic environment does not deliver a broad-quality learning setting to its learners, then it fails in its mission. The educational environment has to gain more influence on how their new learners develop, and the university has to be guarded about how they plan to ascertain that these new entrants become agile learners irrespective of their high school background.